Relaxin has beneficial effects on liver lipidome and metabolic enzymes. Issue 7 (18th June 2021) - Aragón‐Herrera, Alana; Feijóo‐Bandín, Sandra; Moraña‐Fernández, Sandra; Anido‐Varela, Laura; Roselló‐Lletí, Esther; Portolés, Manuel; Tarazón, Estefanía; Lage, Ricardo; Moscoso, Isabel; Barral, Luis; Bani, Daniele; Bigazzi, Mario; et al.
Abstract: Relaxin is an insulin‐like hormone with pleiotropic protective effects in several organs, including the liver. We aimed to characterize its role in the control of hepatic metabolism in healthy rats. Sprague‐Dawley rats were treated with human recombinant relaxin‐2 for 2 weeks. The hepatic metabolic profile was analyzed using UHPLC‐MS platforms. Hepatic gene expression of key enzymes of desaturation (Fads1/Fads2) of n‐6 and n‐3 polyunsaturated fatty acids (PUFAs), of phosphatidylethanolamine (PE) N‐methyltransferase (Pemt), of fatty acid translocase Cd36, and of glucose‐6‐phosphate isomerase (Gpi) were quantified by Real Time‐PCR. Activation of 5′AMP‐activated protein kinase (AMPK) was analyzed by Western Blot. Relaxin‐2 significantly modified the hepatic levels of 19 glycerophospholipids, 2 saturated (SFA) and 1 monounsaturated (MUFA) fatty acids (FA), 3 diglycerides, 1 sphingomyelin, 2 aminoacids, 5 nucleosides, 2 nucleotides, 1 carboxylic acid, 1 redox electron carrier, and 1 vitamin. The most noteworthy changes corresponded to the substantially decreased lysoglycerophospholipids, and to the clearly increased FA (16:1n‐7/16:0) and MUFA + PUFA/SFA ratios, suggesting enhanced desaturase activity. Hepatic gene expression of Fads1, Fads2, and Pemt, which mediates lipid balance and liver health, was increased by relaxin‐2, while mRNA levels of the main regulator of hepatic FA uptake Cd36, and of the essential glycolysis enzyme Gpi, were decreased. Relaxin‐2 augmented the hepatic activation of the hepatoprotector and master regulator of energy homeostasis AMPK. Relaxin‐2 treatment also rised FADS1, FADS2, and PEMT gene expression in cultured Hep G2 cells. Our results bring to light the hepatic metabolic features stimulated by relaxin, a promising hepatoprotective molecule.